2022
DOI: 10.1016/j.aninu.2021.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Flesh quality of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) fed with hydrolyzed porcine mucosa-supplemented low fishmeal diet

Abstract: Iso-nitrogenous and iso-lipidic diets containing 0%, 3%, 6%, 9%, and 12% hydrolyzed porcine mucosa (namely, HPM0, HPM3, HPM6, HPM9, and HPM12) were prepared to evaluate their effects on the growth performance, muscle nutrition composition, texture property, and gene expression related to muscle growth of hybrid groupers ( Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂). Groupers were fed to apparent satiation at 08:00 and 16:00 every day for a total of 56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 70 publications
2
9
0
Order By: Relevance
“…The leucine, lysine, and arginine were the main IAA in the muscles of grouper, and the glutamic acid and aspartic acid were the main dispensable amino acids in this study. This was consistent with existing research findings (Yang et al, 2022). IAA/TAA represents an essential indicator for the nutritional value of aquatic proteins, and the IAA/TAA for high-quality proteins is generally thought to be about 0.4 (Yuan et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The leucine, lysine, and arginine were the main IAA in the muscles of grouper, and the glutamic acid and aspartic acid were the main dispensable amino acids in this study. This was consistent with existing research findings (Yang et al, 2022). IAA/TAA represents an essential indicator for the nutritional value of aquatic proteins, and the IAA/TAA for high-quality proteins is generally thought to be about 0.4 (Yuan et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The main indispensable amino acids in grouper muscle are lysine, leucine and arginine, and the main non-essential amino acids are aspartic acid and glutamic acid, in a recent report published from our team, these amino acid levels were similar to the results of the present study (17). Indispensable amino acid/total amino acid (IAA/TAA) ratio is an important reference indicator for evaluating the nutritional value of aquatic protein, and it is generally considered that the ideal IAA/TAA ratio for high quality protein is about 0.4 (18), the ratio of IAA/TAA in grouper muscle in the present study was ∼0.5, indicating that grouper muscle is a high-quality protein source.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, a more palatable feed will be ingested more quickly, and will allow for lower proportions of costly components, such as proteins (Al-Souti et al, 2019). Yang et al (2021) and Yang et al (2022), when characterizing PMH, observed that more than 88% of molecular peptides have a size smaller than 5000 Da, and of these, most (40.02%) have sizes smaller than 180 Da, among which is a large amount of amino acids, including alanine and glycine, that evoke food-seeking behavior for Acipenser persicus, according to Shamushaki et al (2011), as well as alanine and serine, that act as food stimulants for tilapia (Al-Souti et al, 2019) and are also present in the composition of PMH (Table 2). This may explain the preference of tilapia for the feed with the inclusion of PMH.…”
Section: Discussionmentioning
confidence: 99%
“…Porcine mucosa hydrolyzate (PMH) is an enzymatic hydrolyzate, being a by-product generated from the production process of heparin sodium, an anticoagulant drug (Mateos et al, 2014). This hydrolyzate has a profile of essential and non-essential amino acids, in addition to more than 80% of low molecular weight peptides (Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%